If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-16=-5+2x
We move all terms to the left:
3x-16-(-5+2x)=0
We add all the numbers together, and all the variables
3x-(2x-5)-16=0
We get rid of parentheses
3x-2x+5-16=0
We add all the numbers together, and all the variables
x-11=0
We move all terms containing x to the left, all other terms to the right
x=11
| 96+36+(2x-4)=180 | | 12k=65 | | .17=5k−2 | | r=5r+5=-25 | | (1/3)x+12=3x-3 | | y/4=100y= | | 3x-2/4=2 | | 0.79x3.00=13.27 | | x=0.5/6 | | 4(x+5)+x=7+2x+x+3 | | -6x+7(3x-6)=177 | | 4x+44=11 | | 8y–3=69 | | 2+14x=20x+1.5 | | 2/3h=-16 | | 40=5(z-3) | | 3/2w-5/3=-3/2 | | 7m-11=4+2m | | x+67=92 | | 6x-5(6x+39)=153 | | 7(x)=x+6 | | 8x+8x=-1 | | (3x2-5x+1)=(x2+4x+2) | | 25c2-12=1 | | 24-5-10a=-3(4-7a | | 9y–5=22 | | 8x+8x1=-1 | | x-(52-x)=20 | | 15c=90;c=6 | | -1(-2x+1)=9-14x | | 6x-65=3x+13 | | 3(4n+2)=-2(4n+6) |